Case Report: Complete pathologic response to neoadjuvant immunotherapy-chemotherapy in a patient with RET fusion-positive non-small cell lung cancer - Wang, Yan; Zhang, Yan; Cai, Chenlei; Liu, Xinyu; Ren, Shengxiang; Zhou, Songwen (Frontiers in Oncology, 2026)
RET fusions are rare, and occur in 1%-2% of all non-small cell lung cancer (NSCLC) patients. While neoadjuvant immunotherapy-chemotherapy has demonstrated significant benefit for resectable NSCLC, data remain limited for oncogene-positive NSCLC, particularly for rare alterations like RET fusions. Herein, we present a clinical case of a patient with stage IIIA RET fusion-positive adenocarcinoma who received neoadjuvant nivolumab immunotherapy combined with nab-paclitaxel and carboplatin chemotherapy followed by surgery. The postoperative pathologic results revealed pathological complete response (pCR) and no residual viable tumor cells were observed in lymph nodes. This case validates the clinical activity of immunotherapy-chemotherapy in the neoadjuvant setting, providing a foundation for continued exploration in the treatment of early-stage RET fusion-positive NSCLC.